Contemporary Results Show Repeat Coronary Artery Bypass Grafting Remains a Risk Factor for Operative Mortality - Yap, C.; Sposato, L.; Akowuah, E.; Theodore, S.; Dinh, D.; Shardey, G.; Skillington, P.; Tatoulis, J.; Yii, M.; Smith, J.; Mohajeri, M.; Pick, A.; et al. (2009)
Background: Reoperative coronary artery bypass grafting (redo CABG) shows improving outcomes, but with varying degrees of improvement. We assessed contemporary outcomes after redo CABG to determine if redo status is still a risk factor for early postoperative complications and midterm survival. Methods: Isolated CABG procedures (June 1, 2001 to May 31, 2008) within the Australasian Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database were included. Redo status as a predictor for early outcomes was assessed with logistic regression analysis. Midterm survival was determined from the National Death Index. Effect of redo status on midterm survival was assessed using a Cox proportional hazards model. Results: Inclusion criteria were met by 13,436 patients, and 458 (3.4%) underwent redo CABG. Operative mortality was 4.8% for redo CABG and 1.8% for first-time CABG (p < 0.001). After adjustment, redo status remained a predictor for operative mortality (odds ratio [OR], 2.1; 95% confidence interval [CI], 1.3 to 3.6), myocardial infarction (OR, 2.8; 95% CI, 1.6 to 6.0), and prolonged ventilation (OR, 1.5; 95% CI, 1.1 to 2.0). Unadjusted survival was lower for the redo CABG group vs the first-time CABG group at up to 6 years (p = 0.01, log-rank test. After adjusting for differences in patient variables, redo status was not a predictor of midterm survival (OR, 1.03; 95% CI, 0.78 to 1.35; p = 0.85). Conclusions: Early postoperative outcomes of redo CABG are encouraging. Midterm survival is excellent; however, redo remains a significant risk factor for operative mortality in contemporary practice. © 2009 The Society of Thoracic Surgeons.